Effect of Typhonium flagelliforme Extract on the Viability of Colorectal Cancer Cells HCT-116 - Sadikin, Nadya Audina N; Nazar, M. Ariq; Ibrahim, Sugeng (Stem Cell and Cancer Research (SCCR), 2024)
Background: Colorectal cancer (CRC) remains a significant global health challenge, with rising incidence rates, particularly among younger individuals [1]. Conventional treatments, including chemotherapy and radiation, often cause severe side effects, necessitating the exploration of alternative therapeutic options. Typhonium flagelliforme, a medicinal plant widely used in traditional medicine, has been investigated for its cytotoxic potential against HCT-116 colorectal cancer cells. Objective: This study assessed the cytotoxic effects of T. flagelliforme extract on HCT-116 colorectal cancer cells using the MTT assay. Methods: The cytotoxicity of Typhonium flagelliforme (T. flagelliforme ) extract on HCT-116 colorectal cancer cells was assessed using the MTT assay after 24 hours of treatment with different concentrations (20–100 µg/mL). Results: The findings revealed a dose-dependent reduction in cell viability, with an IC₅₀ value of 73.47 µg/mL, indicating moderate cytotoxic activity. Higher extract concentrations (100–60 µg/mL) significantly decreased cell viability, while the lowest concentration (20 µg/mL) showed a paradoxical increase, possibly due to a hormesis effect. Conclusion: The findings revealed a dose-dependent reduction in cell viability, with an IC₅₀ value of 73.47 µg/mL, indicating moderate cytotoxic activity.